2020
DOI: 10.1177/0363546520972990
|View full text |Cite
|
Sign up to set email alerts
|

Core Strength Training Can Alter Neuromuscular and Biomechanical Risk Factors for Anterior Cruciate Ligament Injury

Abstract: Background: Core stability is influential in the incidence of lower extremity injuries, including anterior cruciate ligament (ACL) injuries, but the effects of core strength training on the risk for ACL injury remain unclear. Hypothesis: Core muscle strength training increases the knee flexion angle, hamstring to quadriceps (H:Q) coactivation ratio, and vastus medialis to vastus lateralis (VM:VL) muscle activation ratio, as well as decreases the hip adduction, knee valgus, and tibial internal rotation angles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 57 publications
3
45
0
Order By: Relevance
“…Additionally, thirteen other potential papers were identified when manually checking the reference lists of the included articles. Only eight fulfilled the inclusion criteria ( Sheerin, Hume & Whatman, 2012 ; Baldon et al, 2014 ; Czasche et al, 2017 ; Araújo et al, 2017 ; McCurdy et al, 2012 ; Jeong, Choi & Shin, 2020 ; Thompson-Kolesar et al, 2017 ; Saad et al, 2018 ). Therefore, a total of ten studies were included in the final review.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, thirteen other potential papers were identified when manually checking the reference lists of the included articles. Only eight fulfilled the inclusion criteria ( Sheerin, Hume & Whatman, 2012 ; Baldon et al, 2014 ; Czasche et al, 2017 ; Araújo et al, 2017 ; McCurdy et al, 2012 ; Jeong, Choi & Shin, 2020 ; Thompson-Kolesar et al, 2017 ; Saad et al, 2018 ). Therefore, a total of ten studies were included in the final review.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, this findings were only limited to females with PFPS (Baldon et al, 2014). Jeong, Choi & Shin (2020) reported that the intervention group showed reduced knee valgus during side-step cutting task following ten weeks of core strength training. This study involved 48 male participants who were assigned randomly to either the intervention or control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing body of research suggests [ 11 , 12 ] that core stability (CS) deficits can have a significant impact on lower limb function [ 13 ]. Based on this idea, poor CS is currently considered a crucial factor in the development of lower extremity injuries, which are usually solely attributed to lower limb malfunction [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%